2013
DOI: 10.1002/jor.22316
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone adaptation to loading in a rabbit model is not magnitude‐dependent

Abstract: Although mechanical loading is known to influence trabecular bone adaptation, the role of specific loading parameters requires further investigation. Previous studies demonstrated that the number of loading cycles and loading duration modulate the adaptive response of trabecular bone in a rabbit model of applied loading. In the current study, we investigated the influence of load magnitude on the adaptive response of trabecular bone using the rabbit model. Cyclic compressive loads, producing peak pressures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(60 reference statements)
2
9
0
Order By: Relevance
“…We only investigated the bone remodeling response up to 14 days of loading, thus focusing on the initial tissue differentiation phase and not long-term bone remodeling. Our loading applied is not in the direction it is normally loaded in vivo such as in knee replacements, perpendicular to the lateral surface of the tibia, 50 as this was deemed not feasible in a rat model. A limitation is that dynamic histomorphometry was not performed and it can detect bone formation at higher resolution than our micro-CT based method.…”
Section: Discussionmentioning
confidence: 99%
“…We only investigated the bone remodeling response up to 14 days of loading, thus focusing on the initial tissue differentiation phase and not long-term bone remodeling. Our loading applied is not in the direction it is normally loaded in vivo such as in knee replacements, perpendicular to the lateral surface of the tibia, 50 as this was deemed not feasible in a rat model. A limitation is that dynamic histomorphometry was not performed and it can detect bone formation at higher resolution than our micro-CT based method.…”
Section: Discussionmentioning
confidence: 99%
“…Axial loading applied between 5N and 13N on mouse tibiae showed significant load magnitude-related increases in cortical bone formation [24]. However, it is with interest to observe that no magnitude dependence on trabecular bone adaptation was found in a cyclic compressive loading study in a rabbit model [25]. In the current study, the observed ImP inductions were found to be positively proportional to DHS cuff pressure, namely, which indicates promising potential of DHS loading dose dependency on ImP related bone adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…( 24 ) However, using a rabbit femoral cancellous loading model, Yang and colleagues found that trabecular bone adaptation to loading is not magnitude‐dependent at the strain levels examined. ( 25 ) The axial tibial loading model can provide a more physiological mechanical environment to examine the effects of loading in both cortical and cancellous bone simultaneously. ( 26 ) Similar to the response observed in other cortical loading models, cortical bone in the tibial loading model is dose‐dependent and governed by a load threshold.…”
Section: Introductionmentioning
confidence: 99%